Dentists’ use of Caries Risk Assessment in Children: Findings from the Dental PBRN - Riley, Joseph L. (2010)
PURPOSE: The overall aim of this study was to quantify dental practice patterns related to caries risk and risk assessment. METHODS: This study surveyed Dental Practice-based Research Network member dentists in four regions in the US and Scandinavia who perform restorative dentistry in their practices. The survey asked a range of questions about caries risk assessment in patients ages 6-18. RESULTS: Seventy-three percent of dentists reported performing caries risk assessment; 14% assess caries risk using a special form. Regions where dentists were most commonly in a private practice model were the least likely to perform caries risk assessment. Regions where most dentists practiced in a large group practice model were the most likely to use a special form for caries risk assessment. More-recent graduates from dental school were more likely to use caries risk assessment when compared to older graduates. Current oral hygiene, decreased salivary flow, and the presence of active caries were rated as the most important caries factors. Some differences by region were also evident for the risk factor ratings. CONCLUSION: These results suggest that not all community dentists assess caries risk. We also observed considerable variability in dentists’ views of the importance of specific caries risk factors in treatment planning and only weak evidence that caries risk assessment is driving clinical practice when preventive treatment recommendations are being considered.